Pengembangan Bahan Ajar Sistem Respirasi Berbasis Pbl Untuk Meningkatkan Pemahaman Kosep, Sikap Dan Perilaku Terhadap Bahaya Merokok - Lisdiana Lisdiana; Noor Aini Habibah; Aini Sa’adah (Departement of Mathematics Education, 2023)
The 2013 curriculum demands that learners be active. One of the efforts is by applying problem-based learning. This research developed effective and valid PBL teaching material about the respiratory system material for XI graders at Islamic Senior High School. This Research & Development validated the teaching material with the assessment sheets of the validator. Then, the researchers analyzed the percentages descriptively. The researchers examined the levels of the teaching material readability within a small-scale test. The large-scale test of the teaching material implementation involved 34 learners from the XI Mathematics & Science program. The test applied conceptual understanding results and the assessment of smoking attitude and avoidance behavior. The results showed the validation score of the media expert was 93.12%. The validation score of the material expert was 89.39%. Then, the biology teacher's validation score was 92.5%. All percentages showed that the product was extremely valid. The conceptual understanding results found higher posttest scores than the pretest score with the N-gain of 0.54, categorized moderate. The attitude assessment score of the smoking behavior based obtained a percentage mean of 86.77%, categorized as extremely high. The avoidance behavioral assessment of smoking obtained a percentage mean of 90,02%, categorized as extremely high. The results showed the teaching material about the respiratory system based on PBL was valid and effective to apply in the eleventh grade of Mathematics Science at MA NU 01 Banyuputih.